Implementasi Protokol S/MIME pada Layanan E-mail Peningkatan Jaminan Keamanan Secara Online pada Kantor PT Tammar Frasti - Nahot Frastian (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Implementation of information system technology has been changing all aspects of human life, such as the human’s way of communicationthat is initially conventional into digital way. E-mail is a service provided by information technology system as a means to exchange information digitally. Even though communicating using e-mail has many advantages,it is vulnerable to digital attackers, such as tapping. Security is the key to securing information containedin e-mail. PT. TAMMAR FRASTI is a business organization that deals with Information Technology infrastructure among private companies that exchange their daily confidential information using e-mail online. S/MIME is one of the alternative security that can be implemented in e-mail. The final result of this research is the design of S/MIME protocol implementation in e-mail service for PT. TAMMAR FRASTI applying cryptographic techniques in the form of digital signatures and / or encryption proven to meet the aspects of information security. By implementing S/MIME, information security aspects such as confidentiality, integrity, authentication and non-repudiation expected by PT. TAMMAR FRASTI may be successfully realized.